Pengaruh Media Canva Berbantuan Artificial Intelligence terhadap Kemampuan Komunikasi Interpersonal dan Motivasi Belajar Akidah Akhlak Peserta Didik di MIN 1 Sidoarjo - Zuha Prisma Salsabila; Adheari Sya'ban Nugrohaji; Hasan Badri; Ahmad Shodiq; Hisbullah Huda (AR-RIAYAH: Jurnal Pendidikan Dasar, 2024)
This study provides a solution because students have low learning motivation in Akidah Akhlak subjects and lack of interpersonal communication skills. This study aims to see how AI-assisted Canva Media has an influence or not on interpersonal communication skills and learning motivation of grade V students at MIN 1 Sidoarjo. The method used is quantitative method with quasi-experimental type and Noneqeuivalent Pretest-Posttest Control Group design. Questionnaires were given as pretest and posttest for data collection. In this study, grade V-A students were used as the experimental group and grade V-B students were used as the control group. The sampling technique was purposive sampling. Descriptive statistical analysis, partial t test, and simultaneous F test were used to analyse the data. The results showed that there was an effect of AI-assisted Canva Media with Interpersonal Communication Skills, a two-tailed Sig value of 0.001, and a two-tailed Sig value of 0.001, respectively showing the effect of AI-assisted Canva Media with learning motivation and both. As a result, H0 is rejected and H1 is accepted.